2018
DOI: 10.1590/1982-2554130963
|View full text |Cite
|
Sign up to set email alerts
|

A presença do filme nacional nas salas de cinema do Brasil: um estudo sobre a codistribuição

Abstract: Este é um artigo publicado em acesso aberto (Open Access) Palavras-chave: cinema brasileiro; mercado; distribuição.Abstract: The presence of national film at cinema rooms in Brazil: a study about co-distributionThe Brazilian film market has shown a growth momentum last years. Recently, co-distribution, i.e., the distribution of a film made by two or more companies at the same time, has been a more frequent strategy. The aim of this paper is to analyze the different ways of acting in the co-distribution of Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Although it has been suggested that the Brazilian film industry seems to be adapting, rather than simply replicating, the North American mode of production nowadays (Brannon Donoghue, 2014), Hollywood's presence is still strongly felt in the Brazilian film market. Due to a systematic deficit of investments in distribution and exhibition, domestic productions are obliterated by the persistent dominance of Hollywood films on cinema screens (Johnson, 1987;Rêgo, 2005), with Brazilian films often failing to widely reach the public (Gimenez and da Rocha, 2018).…”
Section: Creative Policy Making and The Film Industry In Brazilmentioning
confidence: 99%
“…Although it has been suggested that the Brazilian film industry seems to be adapting, rather than simply replicating, the North American mode of production nowadays (Brannon Donoghue, 2014), Hollywood's presence is still strongly felt in the Brazilian film market. Due to a systematic deficit of investments in distribution and exhibition, domestic productions are obliterated by the persistent dominance of Hollywood films on cinema screens (Johnson, 1987;Rêgo, 2005), with Brazilian films often failing to widely reach the public (Gimenez and da Rocha, 2018).…”
Section: Creative Policy Making and The Film Industry In Brazilmentioning
confidence: 99%